Effect of neoadjuvant therapy on serum transforming growth factor-β, squamous cell carcinoma associated antigen, and prognosis in patients with locally advanced esophageal cancer: Effect of NAT on TGF-β, SCC and prognosis in patients with EC - Zhang, Ruirui; Tian, Wenze; Zhao, Huanyu; Zhang, Zhengwei; Wu, Jian; Sun, Su’an; Liu, Haiyan (Cellular and Molecular Biology, 2023)
It was to explore the effect of neoadjuvant therapy (NAT) on serum-related indicators and prognosis of patients with locally advanced esophageal cancer (EC). 400 EC patients were grouped as controls (295 cases, radical EC resection alone) and research group (105 cases, NAT plus radical EC resection). The levels of serum carbohydrate antigen 19-9 (CA19-9), carcinoembryonic antigen (CEA), and cytokeratin 19 fragment antigen 21-1 (CYFRA21-1), programmed death-1 (PD-1), PD-2, transforming growth factor-β1 (TGF-β1), and squamous cell carcinoma (SCC) antigen were detected before and after treatment. The follow-up lasted for 3 years. The quality of life (QoL) was evaluated by QLQ-OES24. The recurrence rate, recurrence time, overall survival rate (SR), disease-free SR, and complication rate were compared. Compared with controls, the levels of serum CA19-9, CEA, CYFRA21-1, PD-1, PD-2, TGF-β1, and SCC were decreased, the QoL score was increased 3 years post-treatment, and the recurrence time was prolonged in the research group (P<0.05). The R0 resection rate, recurrence rate, 3-year overall SR, and disease-free SR of the two groups were 67.12% vs 85.71%, 21.36% vs 6.67%, 56.27% vs 77.14%, 29.83% vs 45.71%, respectively (P<0.05). The complication rates of the two groups were 32.54% and 29.52%, respectively (P>0.05). NAT plus radical resection of EC can effectively reduce the level of serum oncology markers in patients with locally advanced EC, reduce the postoperative recurrence rate, improve QoL and SR, and has high safety.